Study Of The Taxation System In Malaysia (With Reference To Its Structure And Implications - Jasmon, Abadan in Jasmon (2005)
This thesis is a current study of the Malaysian tax regime. It focuses on the three main areas of taxation: personal income tax, corporate income tax and consumption tax, in view of their significant contribution towards the Malaysian goverment revenue and their impact on foreign direct investment. As Malaysia moves up the value ladder, the current tax regime has to face new challenges to attract hitech FDI. For this research, the candidate has chosen a multinational IT company and simulated the financial results under the tax regimes of Malaysia, Singapore, Thailand and Indonesia.